Can Decentralization Affect Public Service Delivery? A Preliminay Study of Local Government’s Innovation and Responsiveness in Indonesia. - Hidayati, Firda (JPAS (Journal of Public Administration Studies), 2017)
Decentralization has helped to increase quality of public service to be more responsive and accountable to its local people, but many still question its effectiveness especially in developing coutries. Since 1998, Indonesia has applied decentralization to manage the government, the drastic shift from strong centralization to decentralization has brought question on its effectiveness. This paper presents normative and empirical evidence on decentralization to public service delivery in Indonesia. It analyzes of curent theories and application that support the scheme on how decentralization may reduce ineficiency and ineffeciveness in public service provision. Drawing from articles, the researcher found that efficiency can be increased by providing institutional change to improve accountablity of public service provision. It is recommended that local government should assign specific local bureaucrats to hold reponsible for certain public service that will lead to strong involvement of society and bureaucrats in improving public service provision. The quick bureaucrat response and proper innovation should create strong public service demand on better public service provision and therefore, put high pressure on elite and bureacrats to be more responsive and accountable in managing this service.